2021
DOI: 10.5551/jat.56390
|View full text |Cite
|
Sign up to set email alerts
|

Serum Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9) is Independently Associated with Insulin Resistance, Triglycerides, Lipoprotein(a) Levels but not Low-Density Lipoprotein Cholesterol Levels in a General Population

Abstract: Proprotein convertase subtilisin/kexin type 9 (PCSK9) has been identified as an important regulator of low-density lipoprotein (LDL) receptor processing. Evolocumab and alirocumab are PCSK9 inhibitors; however, little is known about the association between PCSK9 levels and lipid profiles in a general population. Because PCSK9 inhibitors have LDL-C lowering effects, we investigated whether there is a positive correlation between serum PCSK9 levels and LDL-C or lipoprotein(a) [Lp(a)]. Methods: In Uku town, 674 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 38 publications
1
15
2
Order By: Relevance
“…It has also been reported that PCSK9 level is widely associated with several metabolic determinants 28,43,45,50) . In the present study, PCSK9 level was shown to be positively correlated with waist circumference and levels of triglycerides and HbA1c, and there was an independent association between levels of PCSK9 and triglycerides (Table 4), as previously reported 53) . It has recently been reported that PCSK9 induces degradation of CD36, a membrane transporter of long-chain fatty acids, and affects long-chain fatty acid uptake and triglyceride metabolism in adipocytes and in the liver 54) .…”
Section: Correlation and Multivariable Linear Regression Analyses Forsupporting
confidence: 91%
“…It has also been reported that PCSK9 level is widely associated with several metabolic determinants 28,43,45,50) . In the present study, PCSK9 level was shown to be positively correlated with waist circumference and levels of triglycerides and HbA1c, and there was an independent association between levels of PCSK9 and triglycerides (Table 4), as previously reported 53) . It has recently been reported that PCSK9 induces degradation of CD36, a membrane transporter of long-chain fatty acids, and affects long-chain fatty acid uptake and triglyceride metabolism in adipocytes and in the liver 54) .…”
Section: Correlation and Multivariable Linear Regression Analyses Forsupporting
confidence: 91%
“…This effect has been reversed by the addition of the PCSK9 inhibitor alirocumab suggesting that PCSK9 enhances the secretion of Lp(a) but does not have an effect on its catabolism [44]. Data from epidemiological studies are conflicting: most of them showed no or only a weak association between Lp(a) and PCSK9 concentrations [45][46][47][48][49]. In our study, we did not find a significant association between serum PCSK9 and Lp(a) levels neither in patients nor in controls.…”
Section: The Interaction Between Pcsk9 and Lp(a)contrasting
confidence: 85%
“…Among 4,232 Swedish men and women aged 60 years with 485 ischemic CVD events during 15 years of follow-up, serum PCSK9 levels were linearly positively associated with incident ischemic CVD including myocardial infarction, angina pectoris, chronic CHD, sudden cardiac death, and ischemic stroke 4) . Although Swedish population has generally higher CVD risk than Japanese population 5) , serum PCSK9 level was not higher in the Swedish study (median level: 94.3 ng/ml measured with ELISA) 4) than that in the Japanese population (mean level: 211.2 ng/ml measured with ELISA) 3) . In a Kenyan study with 698 middle-aged adults which reported the positive association of serum PCSK9 level with hepatic enzyme levels and fatty liver disease, serum PCSK9 level was approximately 150 ng/ml in the median 6) .…”
contrasting
confidence: 53%
“…Presently, Hamamura et al examined the association of serum PCSK9 levels with lipid metabolism and insulin resistance in the Japanese general population with a cross-sectional study design 3) . Higher serum PCSK9 level was associated with serum levels of triglycerides and lipoprotein(a) and insulin resistance among the Japanese population that has relatively low CHD risk.…”
mentioning
confidence: 99%